2001
DOI: 10.1038/sj.onc.1204306
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of wild type and mutant ras alleles to Ras specific exchange factors: Identification of factor specific requirements

Abstract: We have investigated the productive interaction between the four mammalian Ras proteins (H-, N-, KA-and KBRas) and their activators, the mammalian exchange factors mSos1, GRF1 and GRP, by using a modi®ed Saccharomyces cerevisiae whose growth is dependent on activation of a mammalian Ras protein by its activator. All four mammalian Ras proteins were activated with similar e ciencies by the individual exchange factors. The H-Ras mutant V103E, which is competent for membrane localization, nucleotide binding, intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…This observation adds to the argument that Ras-GRF1 and Sos1 use somewhat different mechanisms to promote guanine nucleotide exchange on Ha-Ras. A similar conclusion was reached recently in mutagenic studies of GTPases that investigated the basis for signaling specificity differences between Ras-GRF1 (Cdc25 Mm ) and Rap-GEF C3G (44) and Ras-GRP (45).…”
Section: Sos1 and Ras-grf Signaling Specificity Differencessupporting
confidence: 79%
“…This observation adds to the argument that Ras-GRF1 and Sos1 use somewhat different mechanisms to promote guanine nucleotide exchange on Ha-Ras. A similar conclusion was reached recently in mutagenic studies of GTPases that investigated the basis for signaling specificity differences between Ras-GRF1 (Cdc25 Mm ) and Rap-GEF C3G (44) and Ras-GRP (45).…”
Section: Sos1 and Ras-grf Signaling Specificity Differencessupporting
confidence: 79%
“…This region of the protein is highly conserved and could presumably affect its interaction with one or more of the GEFs or one of the numerous downstream effectors or both. While mutations in residues such as D69 or R73 of H-Ras have an impact on the association with GEFs, CDC25 (Segal et al 1995), SOS, or GRP (Nielsen et al 2001), the changes T74I and T74A have been shown not to be critical for interaction with any of these exchange factors (Segal et al 1995;Nielsen et al 2001). Interestingly genetic data suggest that mutations in T74 may be important for proper activation of adenylyl cyclase in yeast (Segal et al 1995), although this seems to vary with the assay conditions (Nielsen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While mutations in residues such as D69 or R73 of H-Ras have an impact on the association with GEFs, CDC25 (Segal et al 1995), SOS, or GRP (Nielsen et al 2001), the changes T74I and T74A have been shown not to be critical for interaction with any of these exchange factors (Segal et al 1995;Nielsen et al 2001). Interestingly genetic data suggest that mutations in T74 may be important for proper activation of adenylyl cyclase in yeast (Segal et al 1995), although this seems to vary with the assay conditions (Nielsen et al 2001). In addition, a single recessive substitution in the position N81 of yeast Ras2 (equivalent to H-Ras T74) does not significantly change the Ras-GEF interaction, although it affects adenylyl cyclase activity as inferred from complementation assays (Hermann-Le Denmat and Jacquet 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The viral H-Ras (Nielsen et al, 2007), N-Ras and K-Ras have been described elsewhere (Nielsen et al, 2001). ATF2 was cloned into pBabe (pB)-Neo at BamHI-SalI site.…”
Section: Plasmidsmentioning
confidence: 99%